Structural Characterization of a Neutralizing Nanobody With Broad Activity Against SARS-CoV-2 Variants - Li, Tingting; Zhou, Bingjie; Luo, Zhipu; Lai, Yanling; Huang, Suqiong; Zhou, Yuanze; Li, Yaning; Gautam, Anupriya; Bourgeau, Salome; Wang, Shurui; Bao, Juan; Tan, Jingquan; et al. (Frontiers in Microbiology, 2022)
SARS-CoV-2 and its variants such as the Omicron continue to threaten public health. The virus recognizes the host cell by attaching its Spike receptor-binding domain (RBD) to the host receptor ACE2. Therefore, RBD is a primary target for neutralizing antibodies and vaccines. Here we report the isolation and biological and structural characterization of a single-chain antibody (nanobody) from RBD-immunized alpaca. The nanobody, named DL28, binds RBD tightly with a KD of 1.56 nM and neutralizes the original SARS-CoV-2 strain with an IC50 of 0.41 g mL-1. Neutralization assays with a panel of variants of concern (VOCs) reveal its wide-spectrum activity with IC50 values ranging from 0.35-1.66 g mL-1 for the Alpha/Beta/Gamma/Delta and an IC50 of 0.66 g mL-1 for the currently prevalent Omicron. Competition binding assays show that DL28 blocks ACE2-binding. However, structural characterizations and mutagenesis suggest that, unlike most antibodies, the blockage by DL28 does not involve direct competition or steric hindrance. Rather, DL28 may use a “conformation competition” mechanism where it excludes ACE2 by keeping an RBD loop in a conformation incompatible with ACE2-binding.